Hiperglikemia Tidak Menyebabkan Perubahan Bobot Badan dan Jumlah Neuron Mienterik Nitrergik Usus Halus Tikus Wistar (Rattus norvegicus) - Amelia Hana; Pudji Astuti; Yuda Heru Fibrianto; Sarmin Sarmin; Claude Mona Airin; Tauhid Tauhid (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2018)
Digestive dysfunction is a common symptom of diabetes. Diabetes can lead to the loss of enteric neurons as well as nerve dysfunction and gastrointestinal complications. There has been no complete report of mienteric nitrergic of small intestines on hyperglycaemia condition, so the purpose of this study was to assess changes of nitrergic neural profile of small intestines on hyperglycemic Wistar strain rats (Rattus norvegicus). Twelve rats were adapted for 3 days, then they were randomly divided into 3 groups namely group I (K-1, as control), group II (K-2), and group III (K-3). Before treatment all rats were fasted for 12 hours, rats K-1 were induced with 1.0 ml of buffer citrate single peritoneal dose; rats K-2 were induced with 40 mg streptozotocin (STZ)/ kg body weight of single peritoneal dose; and rats K-3 were induced with 45 mg STZ /kg body weight of single peritoneal dose. On the 1st and 5th days after STZ induction, blood was collected through the coccigea vein to measure blood glucose levels and weigh the weight. On the day 5th the rats were uthanated with a high dose of ketamine, dissected and taken small intestines (duodenum, jejunum, and ileum) for staining with Nicotinamide Adenine Dinucleotide Phosphate-diaphorase (NADPH-d). Morphometric changes of nitrergic neurons of the small intestine segments were observed. The results showed that on the 5th day increased blood glucose levels of the K-2 and K-3 groups were significantly higher than K-1 (P <0.01). The weight of three groups did not show any significant improvement difference (P> 0.05). The number of neurons in the duodenum, jejunum and ileum of K-2 group increased higher than that of K-1 and K-3 groups. These results indicate that in hyperglycaemic states, the number of nitrergic neurons increases (K-2 group), and there is a significant decrease in the number of neurons (group K-3) compared with K-1 and K-2 groups (P <0.01). The results of this study concluded, that the STZ induction treatment causes hyperglycemia. Hyperglycemia does not affect to the body weight and the number of nitrergic neurons of small intestines in Wistar strain rats (Rattus norvegicus).